Survey Report: Intersections of Mining and Agriculture, Boddington Radius: land use, workforce & expenditure patterns - Hoath, Aileen; Pavez, Luciano (CSIRO Minerals Down Under National Research Flagship, 2013)
There is considerable evidence that the recent strength of Australia’s export oriented mining sector has contributed to economic growth both nationally and in the main mining states and regions although at uneven rates of growth. However investigation and analysis of the internal distribution of costs and benefits from mining within host regions transitioning from agricultural economies has been limited. This document reports results from a survey conducted by the lead author in the Peel Region during March-June 2012 as a part of the Regions in Transition (RiT) project under the umbrella of the CSIRO Minerals Down Under Flagship. The survey examines changing patterns of workforce participation, changing patterns of rural land use, income and expenditure flows and cross-sectoral influences between mining and agriculture. The targeted survey sample comprises adults over 18 years of age either living or working within a radius of approximately 50 km from Boddington town in the most sparsely populated shire of the region, where two separate mineral extraction and processing operations have been undergoing significant expansion. The data reveals that during the RiT project period (2009-2012) these developments triggered a considerable change in the existing socio-economic fabric sustaining proximate towns, communities and individuals. The particularities of the case mean that this report is most relevant to those with a close interest in the future wellbeing of the Boddington 50 km Radius during and beyond the life of current mining operations. The survey also makes a contribution to the wider literature concerning the socio-economic implications of mining. It investigates and confirms the possibility raised by Hajkowicz et al (2011) that the quantifiable benefits of mineral wealth they identify across 71 LGAs may “mask highly localised inequalities and disadvantage”. By providing a nuanced account of the uneven impacts of mining experienced in one region, the survey serves to illuminate the temporally specific economic trends in mining LGAs that Measham and Reeson (2011) identify from ABS statistical data. The findings presented here are undergoing further analysis as a component of an interdisciplinary study at Curtin Graduate School of Business utilizing economic multiplier analysis and qualitative social data to track and map economic impacts of mine operations income expenditure at regional and state level.